Cleavage of the Capsid Protein Precursors of Encephalomyocarditis Virus in Rabbit Reticulocyte Lysates - Shih, Chao-Yun T. (1981)
The cleavage pathway of the three capsid protein precursors of encephalomyocarditis virus, proteins A1, A, and B, was studied in rabbit reticulocyte lysates. Kinetic data suggested that the three proteins were cleaved through a sequential of A1 to A to B.